Desigualdades socioespaciais e expansão urbana em Petrolina/PE : uma análise a partir da morfologia urbana - Oliveira, Joanna Célia Rodrigues (2024)
Brazil's contemporary urban space currently has characteristics that represent a new content, based on the process of globalization which, in turn, redefines the role of medium-sized cities, adding to them an importance for economic consolidation that goes beyond the local/regional level. In this context, the production of urban space presents, from the analysis of its morphology - in this research understood as the combination of urban form and content - characteristics that point to a fragmentation of space that can be apprehended from its socio-spatial inequalities, which acquire unique properties in the context of cities linked to agribusiness production. These contradictions are the result of the actions of different space-producing agents who act on the basis of their interests, which present the dialectic created between use value and exchange value in the context of financial capitalism. In this sense, this research aims to analyze socio-spatial inequalities in the medium-sized city of Petrolina (PE), understood here from the perspective of urban morphology. The method of analysis chosen is historical-dialectical materialism because it makes it possible to understand reality in its multiple determinations, with the aim of achieving concreteness. The analysis techniques are divided into I - theoretical bibliographic survey of the main categories of analysis mobilized here, namely: the production of urban space; urban morphology; urban inequality; social housing; closed residential developments; the peripheries. II - Data collection based on consultations with municipal public bodies in the city of Petrolina (PE); as well as the Brazilian Institute of Geography and Statistics (IBGE); finally, the search for news on local and regional websites and companies; III - Fieldwork carried out in the city of Petrolina. The analysis showed that the urban expansion of the city of Petrolina (PE) takes place to the extent that it deepens different forms of inequality, benefiting, in the process, the interests of the real estate market in conjunction with public authorities and to the detriment of people with low purchasing power.